Advanced introduction to environmental impact assessment - Saunders, Angus morrison- (United States of America : Edward Elgar Publishing, 2018)
Explores the unifying and universal principles at the heart of Environmental Impact Assessment (EIA) wherever it may be practiced worldwide. This overview of the field by Angus Morrison-Saunders emphasizes the big ideas upon which EIA was founded and which remain central to theory and practice today. In a nutshell, EIA is essentially about thinking before acting.
Introduction: setting the scene -- Forms of EIA -- Back to the beginning: EIA and the National Environmental Policy Act 1969 (US) -- A brief reflection on the goals and purpose of EIA -- EIA and decision-making -- Screening and scoping -- Prediction, assessment and mitigation -- Review, approval decision and EIA follow-up -- Spectrum f development and design considerations -- Alternatives and mitigation -- Representing environment -- Engaging with stakeholders -- Science, uncertainty and adaptive management in EIA -- Cumulative impact assessment -- Conclusions.
Includes bibliographical references and index.
Keywords: SUSTAINABLE DEVELOPMENT